The Position of Receivables as The Object of Zakat According to Madzhab Scholars - Abdul Rahman Ramadhan (Westscience Press, 2023)
This research aims to analyze the opinions of the disagreement of the madzhab scholars about the position of receivables as an object of zakat and find the most correct opinion among these opinions. Zakat is an essential element in the Islamic social framework. A lack of understanding of the assets included in the object of zakat will allow a muzakki to miss some of the zakat objects that he should pay. This research uses a qualitative method. The data collection technique used is literature review. The data collected in this research comes from reference books, scientific articles and official websites that contain information on the research topic, namely zakat and Islamic fiqh. The results of this research show that the fiqh scholars agree on the obligation of a muzakki to pay zakat on assets that have reached the niṣāb. But, the madzhab scholars differed on the treatment of muzakki's assets that are on loan or in the hands of another person. The most correct opinion is the opinion of Imam Ahmad, which is that if a muzakki receives the receivable back, he must pay zakat for each year that the asset is in the hands of another person.